Shared mental models and intra-team psychophysiological patterns: a test of the juggling paradigm. Issue 2 (17th January 2017) - Filho, Edson; Pierini, Davide; Robazza, Claudio; Tenenbaum, Gershon; Bertollo, Maurizio
ABSTRACT: We explored implicit coordination mechanisms underlying the conceptual notion of "shared mental models" (SMM) through physiological (i.e., breathing and heart rates) and affective-cognitive (i.e., arousal, pleasantness, attention, self-efficacy, other's efficacy) monitoring of two professional jugglers performing a real-time interactive task of increasing difficulty. There were two experimental conditions: "individual" (i.e., solo task) and "interactive" (i.e., two jugglers established a cooperative interaction by juggling sets of balls with each other). In both conditions, there were two task difficulties: "easy" and "hard." Descriptive analyses revealed that engaging in a dyadic cooperative motor task (interactive condition) required greater physiological effort (Median Cohen's d  = 2.13) than performing a solo motor task (individual condition) of similar difficulty. Our results indicated a strong positive correlation between the jugglers' heart rate for the easy ( r  = .87) and hard tasks ( r  = .77). The relationship between the jugglers' breathing rate was significant for the easy task ( r  = .73) but non-significant for the hard task. The findings are interpreted based on research on SMM and Theory of Mind. Practitioners should advance the notion of "shared-regulation" in the context of team coordination through the use of biofeedback training.